Factors Affecting HIV Test in Public Health Center at Childbearing Age : A Cross – Sectional Analysis of Demographic and Health Survey in Indonesia - Henny Dwi Susanti; Nurul Iffah Arum P; Min-Huey Chung; Ika Rizki Anggraini; Nurul Aini; Tri Lestari Handayani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The National HIV/AIDS Strategy predicts that 86% of people with HIV (PLHIV) worldwide will know their HIV status by 2022, the remaining 14% do not know that they have HIV and still need access to HIV testing services. As an effort to realize the Sustainable Development Goals and to reduce the incidence of HIV/AIDS by 2030, the Indonesian Ministry of Health needs to design and implement appropriate prevention mechanisms related to HIV/AIDS by conducting early detection of HIV, namely by empowering Community Health Centers to provide HIV testing services and counseling. This study aims to analyze the factors influencing HIV testing at Public Health Centers among women of childbearing age in Indonesia. This study uses a cross-sectional design with data from the 2017 Indonesian Demographic Health Survey (SDKI). Data were analyzed using the logistic regression. The variable in this study were demographic sharacteristics and HIV testing. HIV testing at Public Health Centers among childbearing age in Indonesia was at 32.5%. Several factors influencing HIV testing were identified, including region (OR: 1.22, 95% CI: 1.10 - 1.35), wealth index (OR: 0.82, 95% CI: 0.74 - 0.91), residence (OR: 0.82, 95% CI: 0.74 - 0.91), health insurance coverage (OR: 1.15, 95% CI: 1.04 - 1.27), level of knowledge (OR: 0.92, 95% CI: 0.83 - 1.01), stigma (OR: 0.81, 95% CI: 0.73 - 0.90), and AIDS knowledge source from health professionals (OR: 1.90, 95% CI: 1.70 - 2.12). To optimize HIV testing coverage, healthcare workers should enhance awareness by providing comprehensive HIV/AIDS education. This can be done through various media, such as posters, brochures, and community-involved seminars. The government must ensure HIV testing services are accessible in all regions, including rural and remote areas. Additionally, continuous monitoring and evaluation of HIV testing programs at Public Health Centers are necessary. This will help improve and tailor programs to meet community needs and address influencing factors effectively.